Survei penerapan permainan tradisional dalam pembelajaran penjasorkes di Sekolah Dasar Kecamatan Ipuh Kabupaten Mukomuko - Ramadhan Ramadhan (UNIVED Press, Universitas Dehasen Bengkulu, 2020)
This study aims to determine a survey of the application of traditional games in physical education learning in elementary schools in Ipuh sub-district, Mukomuk district in the 2019/2020 academic year. Which is motivated by the fact that some physical education teachers in elementary schools in Ipuh sub-district have not implemented traditional games. This research is a descriptive quantitative research. The method used is a survey. Research instrument in the form of a questionnaire sheet. The subjects of this study were 12 physical education teachers in elementary schools in Ipuh sub-district, Mukomuko district. The data analysis technique used descriptive analysis, which was stated in the form of a percentage. From the results of the survey research on the application of traditional games in physical education learning in elementary schools in Ipuh sub-district, Mukomuko district in the 2019/2020 academic year, the standardized traditional game factors have been applied with a percentage of 71.6%, not applied with a percentage of 28.4%, and game factors. traditional which has not been standardized is applied with a percentage of 50%, not applied with a percentage of 50%. Overall it was applied with a percentage of 60.8%, and not with a percentage of 39.2%.